Challenging the contest vs. scramble dichotomy in social competition: mixed conditions allow disparately ranked monkeys to get equivalent food but experiencing more competition still leads to risk-averse decisions - Fowler, Erica J.; Arseneau-Robar, T. Jean M.; Mutebi, Wilson; Teichroeb, Julie A. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionFood competition is a major cost to group living. Resources vary in quality, distribution, and handling times, exerting differing competitive regimes and varied effects on individual food intake depending on dominance rank.MethodsTo investigate this interplay and the tipping points between purely contest and purely scramble scenarios, we conducted a field experiment on wild vervet monkeys (Chlorocebus pygerythrus), a species with linear, nepotistic intragroup dominance hierarchies. We baited a multi-destination foraging array with a mixture of clumped, preferred and less clumped, less preferred rewards to observe how individuals’ foraging decisions and route choices were affected by the presence and proximity of competitors. In contrast to previous experiments conducted with this group, rewards had minimal handling times and greater quantities to create a mix of scramble and contest competition.ResultsWe found that neither an individual’s dominance rank nor the frequency with which they faced competition from a dominant competitor significantly affected their overall foraging success, suggesting that we were successful in invoking scramble competition. All individuals, regardless of rank, generally chose to prioritize the best reward at the cost of a less efficient route and increased travel time. Nonetheless, encountering dominant competitors in a higher proportion of trials made focal individuals more likely to begin trials at the nearest, less preferred reward, rather than face contest competition for the preferred, more distant platform.DiscussionOur findings suggest that though greater scramble competition minimizes differences in food intake, risk avoidance still exerts powerful effects on the foraging route choices of those experiencing competition.